2012
DOI: 10.1177/0003319711435149
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Leu7Pro Polymorphism Associated With the Metabolic Syndrome and Its Features in Patients With Coronary Artery Disease

Abstract: The metabolic syndrome (MetS) is characterized by constellation of clinical and biochemical features that increase the risk of cardiovascular disease. Neuropeptide Y (NPY) is a neurotransmitter and enhances the development of obesity and other aspects of MetS. We determined the association between NPY Leu7Pro polymorphism and features of MetS in Iranian patients with coronary artery disease (CAD). A total of 550 patients with CAD including individuals with (n = 184) and without MetS (n = 366) were genotyped by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This single nucleotide polymorphism (SNP) has been associated with a large number of conditions related to obesity and metabolic syndrome traits, including increased BMI in adults (194), development of obesity in young adults (195), risk of hypertension (196), high plasma low-density lipoprotein-cholesterol (LDL-c) in children and adults (196, 197), and elevated plasma TAG (198). This variant has been associated with metabolic syndrome in patients with coronary artery disease (199). This SNP has also been shown to correlate with high birth body weight in preschoolers, the risk of an accelerated atherosclerotic process or carotid atherosclerosis in adults (196, 200), and the risk of type 2 diabetes mellitus in adults (201).…”
Section: Implications For Obesity and Metabolic Syndromementioning
confidence: 99%
“…This single nucleotide polymorphism (SNP) has been associated with a large number of conditions related to obesity and metabolic syndrome traits, including increased BMI in adults (194), development of obesity in young adults (195), risk of hypertension (196), high plasma low-density lipoprotein-cholesterol (LDL-c) in children and adults (196, 197), and elevated plasma TAG (198). This variant has been associated with metabolic syndrome in patients with coronary artery disease (199). This SNP has also been shown to correlate with high birth body weight in preschoolers, the risk of an accelerated atherosclerotic process or carotid atherosclerosis in adults (196, 200), and the risk of type 2 diabetes mellitus in adults (201).…”
Section: Implications For Obesity and Metabolic Syndromementioning
confidence: 99%
“…Based on the data from NHANES collected between 1999 and 2002, the prevalence of Met Syndrome is 34.5% (11,12). Also Azimi-Nejad et al found that the "prevalence of Met syndrome was higher in Iranian women (55.0%), followed by Iranian men (30.1%), and this was higher than in French men (13.7%) and French women (6.6%) (13).…”
Section: Contextmentioning
confidence: 99%
“…Based on these findings, the obesogenic role of peripheral Y 2 -receptors seems quite convincing and antagonism of peripheral Y 2 -receptors a plausible anti-obesity drug strategy. To this end, we aimed to test the anti-obesity effects of chronic treatment with a specific Y 2 -receptor antagonist with a potential clinical application to be obesity and metabolic disorders due to NPY excess induced by chronic stress or genetic factors (gain-of-function polymorphisms) ( Karvonen et al, 1998 ; Ding et al, 2005 ; Masoudi-Kazemabad et al, 2013 ). In order to study this, transgenic mice overexpressing NPY in noradrenergic neurons (OE-NPY DβH ) and wildtype (WT) control mice were subjected to chow or DIO with Western type diet and treated with peripheral Y 2 -receptor antagonist, BIIE0246, which is highly selective for its receptors ( Doods et al, 1999 ) and unable to penetrate the blood-brain barrier ( Brothers et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%